Gelatin/monetite electrospun scaffolds to regenerate bone tissue: Fabrication, characterization, and in-vitro evaluation. (January 2023) - Singh, Yogendra Pratap; Mishra, Balaram; Gupta, Mukesh Kumar; Bhaskar, Rakesh; Han, Sung Soo; Mishra, Narayan Chandra; Dasgupta, Sudip
Abstract: This work is dedicated to combining nanotechnology with bone tissue engineering to prepare and characterize electrospun gelatin/monetite nanofibrous scaffold with improved physicochemical, mechanical, and biological properties. Nanofibrous scaffolds possessing fiber diameter in the range of 242–290 nm were prepared after incorporating varying content of monetite nanoparticles up to 7 wt % into the gelatin matrix using the electrospinning technique. Cross-linking of gelatin chains in the scaffold was performed using 0.25 wt% glutaraldehyde as indicated by imine (-CN-) bond formation in the FTIR analysis. With an increase in monetite addition up to 7 wt%, a decrease in swelling ratio and bio-degradability of cross-linked gelatin scaffolds was observed. Gelatin scaffold with 7 wt% monetite content registered the highest values of tensile strength and tensile modulus of 18.8 MPa and 170 MPa, as compared to 0% and 5 wt% monetite containing scaffolds respectively. Cell viability and differentiation were studied after culturing MG-63 cells onto the scaffolds from confocal microscopy of live and dead cells images, MTT assay, and alkaline phosphatase assay for a cell culture period of up to 21 days. It was observed that 7 wt % monetite containing gelatin scaffold exhibited better MG-63 cell adhesion, proliferation, higher biomineralization, and ALP activity compared to 0% and 5 wt% monetite containing electrospun scaffolds studied here. Graphical abstract: Scheme : Schematic representation of the effect of the DCPA concentration up to 7 wt % into the gelatin nanofibrous matrix on the morphology, mineralization, MG-63 cells attachment, and osteogenic properties. Image 1 Highlights: The nanofibrous scaffolds with average fiber diameter varying between 242 and 290 nm were successfully fabricated using the electrospinning technique from gelatin suspension containing 5 wt% and 7 wt% monetite nanoparticles. Monetite nanoparticle incorporation into gelatin matrix up to 7 wt% enhanced the tensile strength and modulus of the nanofibrous scaffolds with respect to its pure gelatin counterpart. Human pre-osteoblasts, MG-63 cells cultured onto monetite embedded gelatin nanofibrous scaffold exhibited better cell adhesion, spreading, proliferation, and osteogenic differentiation over its pure gelatin derivative.